Synthesis and Characterization of Acid-Hydrolyzed Breadfruit Starch (Artocarpus altilis) Nanoparticles as a Potential Carrier for Doxorubicin - Cut Fatimah Zuhra; Siti Rahmawati; Juliati Br. Tarigan (Journal of Chemical Natural Resources, 2025)
Natural starch-based materials are promising for drug delivery due to their biodegradability, abundance, and biocompatibility. This study isolated starch from breadfruit (Artocarpus altilis) and converted into nanoparticles via acid hydrolysis using HCl 2.2 N under shaking incubation at 38°C for 24 hours. The process yielded nanoparticles with a recovery efficiency of 67% and an average particle size of 347.76 nm—within the optimal range for passive tumor targeting via the enhanced permeability and retention (EPR) effect. Compared to native starch, the nanoparticles exhibited enhanced solubility and reduced viscosity, indicating improved aqueous dispersion. FTIR spectroscopy confirmed the retention of major functional groups, while SEM analysis showed distinct changes in surface morphology indicative of granule disintegration. To evaluate pharmaceutical applicability, doxorubicin hydrochloride (DOX) was employed as a model drug. The breadfruit starch nanoparticles achieved a high drug loading efficiency of 78.3%. These results demonstrate the potential of breadfruit starch nanoparticles as a sustainable, low-cost drug delivery platform and highlight the value of underutilized tropical starches in nanomedicine.